Explaining Growth Differences across Firms: The Interplay between Innovation and Management Practices - Livio Romano (European Commission, Joint Research Centre (JRC), 2018)
This paper provides first empirical evidence of the joint effects that innovation strategies and human resource management practices exert on firm growth. By exploiting unique information from a large sample of Italian manufacturing companies in the very recent years, it shows that investing in technology and implementing performance-based pay policies are both positively associated with a significant turnover, employment and labor productivity growth premium. However, their joint adoption does not necessarily sum the two effects. In particular, performance-based rewards boost growth of non-innovators and of firms pursuing relatively simple innovation strategies, centered around the acquisition of embodied technology. For firms strongly relying on R&D as an additional lever for product and process upgrading, the estimated effect of having in place monetary incentive mechanisms is null or even negative.
Keywords: L20; M21; O30; 330; Heterogeneity; Innovation; Management Practices; Firm Growth